Preserving the Umbundu Language (Global Journal of Human-Social Science, 2023)
The present article discusses the current sociolinguistic situation of the city of Kuito the capital of Bi province from a historical perspective Specifically it examines the use of the Umbundu language among the inhabitants of Kuito In addition to presenting historical information of the linguistic contact between the Portuguese and the Umbundu languages this article also presents the linguistic situation surveyed at the time of the 2014 population census as well as data from another study that show the diminishing use of Umbundu as a communication language This AL has gone from L1 for the older generation to L for more recent generations
Keywords: first language (l1) - second language (l2) - angolan languages (al) - linguistic contact